Unraveling Past Submarine Eruptions by Dating Lapilli Tuff-Encrusting Coralligenous (Actea Volcano, NW Sicilian Channel) - Lodolo, Emanuele; Renzulli, Alberto; Cerrano, Carlo; Calcinai, Barbara; Civile, Dario; Quarta, Gianluca; Calcagnile, Lucio (Frontiers in Earth Science, 2021)
The dating of young submarine volcanic eruptions, with their potential generation of tsunamigenic waves, is essential for a reliable hazard assessment. This is particularly relevant in highly populated coastal areas. The scarce knowledge of the underwater environment makes however, this reconstruction challenging. Our study is focused on the NW sector of the Sicilian Channel, where several small- and medium-size volcanic edifices are present. The only documented Surtseyan-type eruption occurred in A.D. 1831, forming the ephemeral Ferdinandea Island. Late Pleistocene to mid-Holocene eruptions have been up to now only hypothesized, and based solely on indirect data. Here we present the first radiocarbon dates of a coralligenous bioconstruction sampled at 34 m water depth from the summit of the Actea volcano, grown up progressively (up to nowadays) on a lapilli tuff deposit. Actea volcano is a recently discovered pyroclastic cone located at only four nautical miles off the SW coast of Sicily. The oldest age of the bioconstructions that started to encrustate the shallow water pyroclastics shortly after their emplacement (7,387 ± 175 cal years B.P.) represents a terminus ante quem, thus testifying a mid-Holocene submarine eruption in this sector of the Sicilian Channel. This method may be effectively used to bridge the gap between historical accounts and the geological record and thus may contribute to a better volcanic hazard assessment of submarine eruption and related phenomena such as tsunamis.